The rare entity of cystadenocarcinoma (CAC) in parotid gland: A single-center experience. Issue 5 (May 2019) - Guo, Bing; Cao, Yu-an; Qin, Xingjun; Ma, Chunyue
Abstract: Purpose: Cystadenocarcinoma (CAC) is an extremely rare disease in parotid gland. This study aimed to identify the clinical characteristics of CAC, and the therapeutic options for its treatment. An attempt was also made to identify postoperative recurrence-related risk factors. Material and methods: A retrospective study was conducted of CAC patients treated between 2008 and 2018. Predictive factors for postoperative recurrence (5-year RFS rate) were preliminarily filtered by Kaplan–Meier analysis and then further confirmed by a Cox regression model. Postoperative recurrence was defined as the primary outcome variable and was measured using both univariate and multivariate analysis. Results: A total of 27 patients were analyzed, and the total incidence of postoperative recurrence was 33.3% (9/27). In the Cox regression analysis, patients who received a superficial parotidectomy were 0.046 times more likely to develop tumor relapse than those who only underwent enucleation ( p  = 0.032; 95% CI: 0.003–0.070). The chances of tumor recurrence in patients with the cribriform subtype were 9.701 times that for cases with a papillary pattern ( p  = 0.016; 95% CI: 1.517–62.030). The risk of postoperative recurrence increased abruptly, with an OR of 6.373 ( p  = 0.042; 95% CI: 1.070–37.965), when LN metastasis was found in patients. Conclusion: Preoperative diagnosis of CAC in parotid gland is extremely important for allowing surgeons to apply appropriate therapeutic strategies (enucleation or superficial parotidectomy). Patients with LN metastasis, cribriform pattern, and Ki-67 positivity should be treated further to avoid tumor relapse.